Arnold Bennett’s Naturalistic and Democratic Interiors in The Old Wives’ Tale (1908) - Laurent Mellet (Cahiers Victoriens et Edouardiens)
We know the terms in which Virginia Woolf dismissed Edwardian writers for relying exclusively on materialism. However, another take on Arnold Bennett’s specific approach to objects and interior spaces is made possible by a reappraisal of his naturalistic method. This type of Edwardian fiction reveals a political agenda buoyed up by an empirical narrative praxis. Drawing on Bennett’s The Old Wives’ Tale (1908), we show that Edwardian literary interiors turn into literary tools from which considering oneself, the others and the world out there, differently. Interiors in this novel should be read in spatial, physical, and narrative terms, since Bennett invents new modes of dwelling in order to endow his characters with new ways of narrating themselves. The Baines sisters literally and literarily are the place they inhabit, to the point of being unaware of any distinction between inside and outside. The main narrative strategy of the book is inflected by a centripetal movement that makes us move down and within various forms of interior places and narratives, in which interiority leads to unexpected intimate moments. Seeing, understanding and taming interior places so as to assert oneself narratively and intimately: such is the gist of Bennett’s democratic literary proposition. This is how his naturalism based on an empirical art of the narrative and a surprising use of interior monologue gestures towards a democratic opening of literature in which doorframes, windows and thresholds help us reconsider the aesthetic and political meanings of interiority.